Antialgal Synergistic Polystyrene Blended with Polyethylene Glycol and Silver Sulfadiazine for Healthcare Applications. (25th November 2021) - Anjum, M. Raheel; Mushtaq, Shehla; Abbas, M. Asad; Mahmood, Azhar; Nasir, Habib; Janjua, Hussnain A.; Malik, Qamar; Ahmad, Nasir M.
Abstract : Polystyrene (PS) was blended with polyethylene glycol (PEG) and silver sulfadiazine (SS) with different weight proportions to form polymeric blends. These synthesized blends were preliminary characterized in terms of functional groups through the FTIR technique. All compositions were subjected to thermogravimetric analysis for studying thermal transition and were founded thermally stable even at 280°C. The zeta potential and average diameter of algal strains of Dictyosphaerium sp. (DHM1), Dictyosphaerium sp. (DHM2), and Pectinodesmus sp. (PHM3) were measured to be -32.7 mV, -33.0 mV, and -25.7 mV and 179.6 nm, 102.6 nm, and 70.4 nm, respectively. Upon incorporation of PEG and SS into PS blends, contact angles were decreased while hydrophilicity and surface energy were increased. However, increase of surface energy did not led to decrease of antialgal activities. This has indicated that biofilm adhesion is not a major antialgal factor in these blended materials. The synergetic effect of PEG and SS in PS blends has exhibited significant antialgal activity via the agar disk diffusion method. The PSPS10 composition with 10 w / w % PEG and 10 w / w % SS has exhibited highest inhibition zones 10.8 mm, 10.8 mm, and 11.3 mm against algal strains DHM1, DHM2, and DHM3, respectively. This thermally stable polystyrene blends with improved antialgal properties have potential for a wide range of applications including marine coatings.